Does the adhesive strategy influence the post-operative sensitivity in adult patients with posterior resin composite restorations?. Issue 9 (September 2015) - Reis, Alessandra; Dourado Loguercio, Alessandro; Schroeder, Marcos; Luque-Martinez, Issis; Masterson, Danielle; Cople Maia, Lucianne
Highlights This study address the role of adhesive strategy (ER and SE) on the postop sensitivity. 55% of the clinical trials on this field were considered to be of high or unclear risk of bias. The adhesive strategy (ER or SE) does not influence the postop sensitivity in posterior resin composite restorations.